Dynamic DNA methylation changes reveal tissue-specific gene expression in sugarcane - Xue, Yajie; Zou, Chengwu; Zhang, Chao; Yu, Hang; Chen, Baoshan; Wang, Haifeng (Frontiers in Plant Science, 2022)
DNA methylation is an important mechanism for the dynamic regulation of gene expression and silencing of transposons during plant developmental processes. Here, we analyzed genome-wide methylation patterns in sugarcane (Saccharum officinarum) leaves, roots, rinds, and piths at single-base resolution. DNA methylation patterns were similar among the different sugarcane tissues, whereas DNA methylation levels differed. We also found that DNA methylation in different genic regions or sequence contexts plays different roles in gene expression. Differences in methylation among tissues resulted in many differentially methylated regions (DMRs) between tissues, particularly CHH DMRs. Genes overlapping with DMRs tended to be differentially expressed (DEGs) between tissues, and these DMR-associated DEGs were enriched in biological pathways related to tissue function, such as photosynthesis, sucrose synthesis, stress response, transport, and metabolism. Moreover, we observed many DNA methylation valleys (DMVs), which always overlapped with transcription factors (TFs) and sucrose-related genes, such as WRKY, bZIP, WOX, SPS, and FBPase. Collectively, these findings provide significant insights into the complicated interplay between DNA methylation and gene expression and shed light on the epigenetic regulation of sucrose-related genes in sugarcane.